Understanding preservice teachers' affective responses to VR-enabled scientific experiments - Xie, Tao; Zhang, Ling; Liu, Geping (Frontiers in Psychology, 2022)
Preservice teachers’ preparedness, perception, and affect towards certain technology systems influence the student acquisition of science knowledge, process skills, teaching innovation, and willingness to use technology in their classroom. The purpose of this study was to explore teachers’ affective responses to a virtual reality-enabled scientific experiment (VaSE) system. Fifty-one preservice teachers majoring in educational technology participated in the study. They were divided into two groups and their reactions were measured separately on two occasions. The first occasion used a standard system following the principle of Donald Norman’s affective design model (ADM). The VaSE system was then revised with a strict version of ADM before the participants’ reactions were measured for a second time. The positive and negative affect scale (PANAS) was utilized for affective state evaluation. Semi-structured interviews that focused on affective experiences were organized using an ADM framework and conducted immediately after the participants used VaSE. The results indicated that the positive affect experienced by the preservice teachers was significantly enhanced, and the negative affect was significantly weakened. Academic level, gender, and prior experience were important random effect factors that impacted affective experience. It was also revealed that participants were more likely to be affected by immersion and interactivity in terms of enhancing positive affect and were more likely to be affected by behavioral layer elements in terms of weakening negative affect. Conclusions have been drawn to provide theoretical and practical suggestions for training preservice teachers in ways that improve their ability to integrate technology into the classroom.